FeRu-based metal–organic framework bifunctional catalysts for hydrogen production and methanol electroreforming. Issue 6 (23rd January 2023) - Ling, Qi; Zhao, Ziwei; Li, Ziliang; Yan, Kui; Ding, Chunsheng; Chen, Peng; Sun, Zhaoqi; He, Gang; Lv, Jianguo; Zhang, Miao
Abstract : FeRu-MOF/NF was prepared via one-step solvothermal method on nickel foam (NF). Bifunctional electrode FeRu-MOF (100 : 3)/NF‖FeRu-MOF (100 : 3)/NF showed excellent performance in methanol–water electrolyte with >90% Faraday efficiencies for both cathode and anode products. Abstract : Conventional water electrolysis has significant safety risks associated with it, and the reaction efficiency is limited by the slow kinetics of the anodic oxygen precipitation reaction. The coupling of organic electroreforming and electrochemical hydrogen evolution can generate hydrogen and value-added chemicals. By growing FeRu metal–organic framework nanosheets in situ on a nickel foam, a methanol water co-electrolysis system that can generate hydrogen and oxidize methanol to formate was created. The complete mixing and dispersal of Fe- and Ru-MOFs allows the effective transfer of charge during redox reactions and dispersion of active metal ion sites. The electrocatalyst with the Fe/Ru molar ratio of 100 : 3 in a two-electrode system requires a cell voltage of only 1.40 V at 10 mA cm −2 in 1 M KOH containing 4 M methanol, much lower than that of the conventional overall water splitting system (1.53 V at 10 mA cm −2 ), and the Faraday efficiency of the anode and cathode could exceed 90% for formate and hydrogen generated.